SIKEPI (Coffee Financial System): Innovative Platform as a Form of Financial Digitalization of the Karangpring Village Coffee Farming Community - Aziz, Nur Kholik; Gustin, Revalia (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Karangpring Village has significant potential in coffee commodities, with robusta, arabica, and liberica varieties. This potential makes the village an icon in the national coffee world. Advances in technology and digitalization offer solutions to facilitate daily activities, including in the agricultural sector. Karangpring Village requires the implementation of technology and digitalization to strengthen its superior coffee commodities. The current practice of recording village community finances is still simple and conventional, so digitalization is needed to modernize the process, which is expected to stimulate economic growth and increase the selling value of coffee. This study proposes the SIKEPI (Coffee Financial System) application, which is designed with a simple accounting system so that it is easy to understand and implement by the community. Through socialization, training, and personal assistance, it is hoped that coffee farmers in Karangpring Village can improve digital literacy and accounting understanding through the SIKEPI application.